Studies on the properties of epoxy-oxothiolane resins - Czub, P.; Kowalski, G.; Pielichowski, J. (Polimery, 2022)
Bis-l,3-oxothiolane-2-thione resins (Scheme 1) were prepared in the reactions of commercial low-M epoxy resins, Epidian 5 and Epidian 6, with carbon disulfide. Compositions including Epidian 5 or 6 and various amounts (5, 10, 20, 30 or 40 wt. %) of oxothiolane resins as additives were prepared and cured with piperidine. Mechanical properties such as bending, compressive, tensile and impact strengths were determined. Water absorbency, combustibility and thermal stability were also determined. Addition of 5 to 10 wt. % of sulfur-containing resin was found to improve mechanical strength by 15% (Fig. 1) and thermal stability by 35"C (Table 3, Fig. 3).